The Importance of Nonequilibrium to Equilibrium Transition Pathways for the Efficiency and Stability of Organic Solar Cells. Issue 17 (28th March 2022) - Xin, Jingming; Feng, Jirui; Lin, Baojun; Naveed, Hafiz Bilal; Xue, Jingwei; Zheng, Nan; Ma, Wei
Abstract: Controlled morphology of solution‐processed thin films have realized impressive achievements for non‐fullerene acceptor (NFA)–based organic solar cells (OSCs). Given the large set of donor–acceptor pairs, employing various processing conditions to realize optimal morphology for high efficiency and stable OSCs is a strenuous task. Therefore, comprehensive correlations between processing conditions and morphology evolution pathways have to be developed for efficient performance and stability of devices. Within the framework of the blend system, crystallization transitions of NFA molecules are tracked utilizing the first heating scan of differential scanning calorimeter (DSC) measurement correlating with respective morphology evolution of blend films. Real‐time dynamics measurements and morphology characterizations are combined to provide optimal morphology transition pathways as NFA molecules are shown to be released from the mixed‐phase to form balanced ordered packing with variant processing conditions. Polymer:NFA films are fabricated using blade coating incorporating solvent additive or thermal annealing as processing conditions as a correlation is formulated between performance and stability of solar cells with morphology transition pathways. This work demonstrates the significance of processing condition‐controlled transition pathways for the realization of optimal morphology leading to superior OSC devices. Abstract : Processing condition‐controlled morphology is demonstrated to evolve toward the equilibrium state via phase separation and the crystallization pathway in PBDB‐T:IT‐M organic solar cells (OSCs). The cold crystallization behavior of IT‐M reflects the subtle changes in different pathways and further correlates with morphology data. The impact of the transition pathway on device performance and stability indicates its importance in instructing device optimization.